An empirical study on the relationship between economic growth and forest carbon sink value based on PVAR model - Song, Yukun (Frontiers in Energy Research, 2023)
The dynamic relationship between the value of forest carbon exchange and economic growth has a significant impact on the sustainable development of China’s economy and society. Hence, the consequences cannot be ignored even when China enjoys a win-win situation concerning environment and development. This study examines the economic growth and forestry data from 1995 to 2020 (2021 data from the Statistical Yearbook of China Forestry and Grassland in February 2023 has not been released) to calculate the forest carbon sink (using the forest stock method), estimate the forest carbon sink price, and establish a panel vector autoregression model. Pulse response analysis and variance decomposition are also used to test the dynamic relationship between economic growth and forest carbon sink value. The study finding reveal that during the research period, economic growth promoted the development of forest carbon sinks; forest carbon sinks “suppressed” economic growth in the short term; and the inhibitory effect of forest carbon sinks is no longer significant. The possible innovations and contributions of this study are: 1) Expanding relevant research on the calculation of the value of forest carbon exchange, using the forest accumulation method to calculate the province’s forest carbon exchange, and using the production function of the number to estimate the price of forest carbon exchange. 2) Based on the requirements of the high-quality development stage of the economy, it can serve as a reference to formulate and improve policies for relevant departments (according to the empirical results), thereby helping the country achieve the “dual carbon” goal as soon as possible.